The first observed bloom of the diatom Dactyliosolen fragilissimus (Bergon) Hasle 1996 in the Gulf of Gdańsk - Maria Łotocka (Oceanologia)
The diatom Dactyliosolen fragilissimus (Bergon) Hasle 1996(syn. Rhizosolenia fragilissima Bergon 1903) occurs in thewestern Baltic Sea predominantly in summer, sometimes formingblooms. In autumn 2005, numerous D. fragilissimus cells wereobserved for the first time in the coastal waters of the Gulfof Gdańsk. In November 2005 a bloom was formed: at its peak,the diatom count was 1.1 × 106 cells dm-3 and its biomasswas 8.9 mg dm-3.